Mini-game design and development – ‘memories’ application - Sannabhadti Shipra Deepak (Nanyang Technological University, 2022)
With increasing life expectancy and low fertility rates, Singapore, similar to other countries in the Global North, faces a rapidly aging population [1]. As a consequence, the Government of Singapore invested $3 billion from 2015 to 2019 to care for elderly Singaporeans [11]. Research and government institutions have evidently been making sizable investments in technology and systems to aid comfortable aging.